Miliary Osteoma Cutis: A Case Report - Felipe Aguinaga; Beatriz Trope; Juan Piñeiro-Maceira; Marcia Ramos-e-Silva (Case Reports in Dermatological Medicine)
The authors present a rare case of osteoma cutis miliaris and briefly update the current knowledge about its clinic, pathogenesis, and therapeutic options.